1996
DOI: 10.1017/s026646660000685x
|View full text |Cite
|
Sign up to set email alerts
|

Using Bootstrapped Confidence Intervals for Improved Inferences with Seemingly Unrelated Regression Equations

Abstract: The usual standard errors for the regression coefficients in a seemingly unrelated regression model have a substantial downward bias. Bootstrapping the standard errors does not seem to improve inferences. In this paper, Monte Carlo evidence is reported which indicates that bootstrapping can result in substantially better inferences when applied to f-ratios rather than to standard errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…For example, Rilstone and Veall (1996) provide encouraging evidence on the performance of certain bootstrap procedures in the context of seemingly unrelated regressions, and Inoue and Kilian (2002) do so in the context of vector autoregressions. But in neither case, and even less so for simultaneous equations models, should we expect the sort of astonishingly good performance that was observed in Figure 3.…”
Section: Simultaneous Equations Modelsmentioning
confidence: 97%
“…For example, Rilstone and Veall (1996) provide encouraging evidence on the performance of certain bootstrap procedures in the context of seemingly unrelated regressions, and Inoue and Kilian (2002) do so in the context of vector autoregressions. But in neither case, and even less so for simultaneous equations models, should we expect the sort of astonishingly good performance that was observed in Figure 3.…”
Section: Simultaneous Equations Modelsmentioning
confidence: 97%
“…However, Wald tests face a number of statistical problems; in particular, (i) the tendency to over-reject the null hypothesis in system OLS and SUR models, and (ii) the non-invariance of nonlinear Wald test statistics to the mathematical reformulation of the null. To address the first issue, we estimate the appropriate p-value of the test statistic using the percentile-F interval of the statistic based on its bootstrap distribution, which has been shown to significantly reduce the over-rejection bias in this setting (Rilstone and Veall 1996). 21 To address the second issue, we assess the robustness of our inferences by constructing linear Wald tests based on the system of parametric versions of the z-conditional demand functions, which we discuss below.…”
Section: Tests Based On Standard (Unconditional) Demand System Estimamentioning
confidence: 99%
“…Atkinson and Wilson, 1992) have shown that bootstrapped standard errors for the SUR model are also biased downwards and therefore cannot improve the situation. However in a recent paper Rilestone and Veall (1996) present Monte Carlo evidence that the bootstrap performs substantially better when applied to t-ratios (i.e. utilizing the so called percentile-t bootstrap) rather than to standard errors.…”
Section: Kh Ghwhuplqdqwv Ri H[fkdqjh Udwh H[srvxuh Dqg Wkh Lpsdfw Rimentioning
confidence: 99%